Implementasi Program Jaminan Sosial Ketenagakerjaan bagi Tenaga Kerja Bukan Penerima Upah di BPJS Ketenagakerjaan Padang - Firdausi, Fakhri Ahmad; Putera, Roni Ekha; Yoserizal, Yoserizal (Journal of Social and Policy Issues, 2023)
The existence of high threats and work risks that can occur at any time to the entire workers can have an impact on the welfare of workers. Therefore, there is a need for social protection for workers so that they can be protected from all threats and risks resulting from work. Especially for the Non-wage workers in Padang city which number of Non-wage workers in Padang city is quite high. Program of BPJS Employment is a government effort to fulfill the basic rights of citizens to obtain protection from various socio-economic risks resulting from work threats. This research aims to know how the implementation of employment social security program for Non-Wage workers at BPJS Employment Padang City. This study uses a qualitative approach with a descriptive method. Data collection techniques were conducted through interview, observation, and documentation. This research uses the theory of Van Meter and Van Horn, which consists of six variables: policy standards and objectives, resources, characteristics of implementing agents, inter-organizational communication, attitudes or tendencies of implementers, and social, economic, and political environmental conditions. Based on the research findings, the researcher concludes that the implementation of the Employment Social Security Program for Non-Wage Workers at BPJS Employment in Padang City has been implemented, but its application is still not optimal. There are still several obstacles in the implementation of the BPJS Employment Program, such as the lack of human resources in program implementation. Furthermore, there is a lack of knowledge and understanding, as well as misunderstandings among the public regarding the BPJS Employment Program. In addition, there is inconsistent communication and coordination with labor institutions and organizations, and the presence of other insurance institutions that may hinder the implementation of the BPJS Employment Social Security Program.